HUBUNGAN KARAKTERISTIK IBU DENGAN STATUS GIZI BALITA DI GAMPONG DAYAH BARO KECAMATAN KRUENG SABEE KABUPATEN ACEH JAYA - Bustami Bustami; Amiruddin Amiruddin (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
Nutritional problems are influenced by many factors that influence each other in a complex manner. At the household level, nutritional conditions are influenced by the household's ability to provide food in sufficient quantities and types as well as parenting patterns which are influenced by factors such as age, education, knowledge, behavior and household health conditions. The aim of the research was to analyze the relationship between maternal characteristics and the nutritional status of children under five. The type of research is analytical. The population is mothers and toddlers 2 – 5 years old. The sampling technique was Total Sampling, namely 61 respondents. Data analysis using the Chi-Square test. The research results showed that there was no relationship between age and the nutritional status of toddlers (p=0.264). There is a significant relationship between maternal education and the nutritional status of toddlers (p=0.000). There was no significant relationship between work and the nutritional status of children under five (p=0.100). There is a relationship between maternal knowledge and the nutritional status of toddlers, (p=0.000). To further improve the nutritional status of toddlers, health cadres and health workers at community health centers are very necessary in efforts to empower mothers so they can practice good parenting patterns, detect early nutritional problems in toddlers and be able to overcome nutritional problems in toddlers.